Readiness to change associated with job performance among health information management professionals during the covid-19 pandemic - Nauri Anggita Temesvari; Mieke Nurmalasari; Deasy Rosmala Dewi; Suprobowati Suprobowati (Rifa'Institute, 2022)
Health information management professionals (HIM professionals) are one of the essential health workers during the Covid-19 pandemic in managing patient data in hospitals. Changes in both policies and work systems were felt by HIM professionals during the Covid-19 pandemic. The impact of these changes influences the job performance of HIM professionals. This study aimed to assess the association between readiness to change and job performance among HIM professionals during the Covid-19 pandemic in RSAB Harapan Kita, Indonesia. The indicators of job performance are quality, timeliness, need for supervision, responsibility, cost-effectiveness, quantity, interpersonal impact, and empathy. The readiness to change in this study seen from self-efficacy, appropriateness, management support, and personal benefits. This study applied a mixed-methods design to assess the association between readiness to change and job performance in which respondents fill out a questionnaire independently via Google Form. Furthermore, a focus group discussion was conducted to probe deeper into what changes occurred during the Covid-19 pandemic and how these changes related to the job performance of HIM professionals. The questionnaire used in previous research has been validated. The samples used were all 27 HIM professionals and 11 of them agreed to continue the focus group discussion. Statistical analysis used the chi-square test on SPSS version 26 to assess the association between variables. The results show that readiness to change indicated significant association with job performance (p=0.001). Informants stated that changes that occurred during the Covid-19 pandemic included the use of personal protective equipment, spraying disinfectants on medical forms and workspaces, and adding Covid-19 reporting both internally and externally.